2020
DOI: 10.1002/mop.32719
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of tunable multistacked metamaterial‐based graphene grating

Abstract: We present a tunable multistacked metamaterial‐based graphene grating structure for the lower THz frequency range. Circular gold wire is placed between graphene layers to obtain wideband response. Reflectance, transmittance, absorption, and refractive index parameters are analyzed for metamaterial‐based graphene grating structure. The results show wideband reflectance response ranging from 1 to 2.5 THz frequency. Reflectance in grating can be controlled by different chemical potentials of the graphene sheet. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…Tunable multi-stacked-based THz absorber based on graphene-grating Parmar et al reported a tunable multi-stacked THz absorber based on graphene grating for the FIR frequency range [93]. The design of the implemented structure is presented in Fig.…”
Section: Thz Absorbermentioning
confidence: 99%
“…Tunable multi-stacked-based THz absorber based on graphene-grating Parmar et al reported a tunable multi-stacked THz absorber based on graphene grating for the FIR frequency range [93]. The design of the implemented structure is presented in Fig.…”
Section: Thz Absorbermentioning
confidence: 99%